2007
DOI: 10.1021/la063316e
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Cu Nanobelt and Ag Belt-Like Materials by Surfactant-Assisted Galvanic Reductions

Abstract: We demonstrate the syntheses of single crystalline Cu nanobelt and Ag belt-like materials via CTAC-assisted (CTAC, cetyltrimethylammonium chloride) galvanic reductions. The single crystalline face-centered cubic phase Cu nanobelt was prepared by reacting CuCl2(aq) with Al(s) in an aqueous solution of CTAC and HNO3. The Cu nanobelt exhibited a high-quality ribbon-like nanostructure with a thickness less than 15 nm, a width of 30-150 nm, and a length up to 10 microm. The belt-like Ag, with a thickness less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Chakraborty et al [39] underlined the importance of the control of growth kinetics prior to the size effect and concluded that the former is enough to obtain any of the three polytypes of Ag. Huang et al [45] successfully fabricated belt-like 4H Ag and suggested that the reason why 4H Ag is rarely observed is probably due to a special combination of synthesis parameters. Similar interpretation of why 4H Ag is favored under our experimental condition could be applied.…”
Section: Formation Of Ag-au Nanostructuresmentioning
confidence: 99%
“…Chakraborty et al [39] underlined the importance of the control of growth kinetics prior to the size effect and concluded that the former is enough to obtain any of the three polytypes of Ag. Huang et al [45] successfully fabricated belt-like 4H Ag and suggested that the reason why 4H Ag is rarely observed is probably due to a special combination of synthesis parameters. Similar interpretation of why 4H Ag is favored under our experimental condition could be applied.…”
Section: Formation Of Ag-au Nanostructuresmentioning
confidence: 99%
“…To our knowledge, HCP crystal structures appear in silver nanowires prepared by electrochemical deposition [17-19] or by simply heating or evaporating FCC-Ag nanowires or nanoparticles [20,21]. Various metal nanostructures containing HCP structures with different morphologies including Ag belts [22], prisms [23], needles [24], rices [25], Au square sheets [26], and tadpoles [27] have been researched. As to crystal structure composition, except the researches [18,26] in which the composition are exclusively HCP, HCP coexists with FCC in most of the aforementioned reports.…”
Section: Introductionmentioning
confidence: 99%
“…The Fast Fourier Transform (FFT) image of the AgNBs, shown in the inset of Fig. 4b, also demonstrates that the growth direction is <200> which is different from the direction <110>, the typical direction of growth that is reported in literature910131821. Thus, because of this different growth direction, unique applications of the AgNBs could be expected in various fields, including catalysis, photo-electronics, and conductive material fabrications, as AgNBs are known to exhibit diverse properties that depend on the growth faces22.…”
Section: Resultsmentioning
confidence: 81%